The Effect of Deep Breathing Exercise on the Level of Dyspnea in Heart Failure at the Depok City Hospital: Deep Breathing Exercise Terhadap Tingkat Dyspnea Pada Gagal Jantung di Rumah Sakit Wilayah Depok - Mardhiyatul Jamilah; Mutarobin (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Heart failure is a chronic, progressive disease that occurs when the heart muscle can't pump enough blood to meet thebody's need for blood and oxygen. Heart failure is caused by problems with heart function, valve disease, or anythingthat can block blood flow in the context of fluid retention resulting in pulmonary congestion, peripheral edema, shortnessof breath, and fatigue. Efforts to control the symptoms experienced by heart failure patients by doing deep breathingexercise. This study aims to determine whether there is an effect of deep breathing exercise on reducing dyspnea in heartfailure patients at the Depok Regional Hospital. This type of research uses a quasi-experimental research design with apretest posttest with control group approach involving 34 respondents with a purposive sampling technique. The researchmeasuring tool uses a modified borg scale. Intervention by giving deep breathing exercise 15 times which is done 3 timesa day for 3 days. The results of the study found that there was an effect of deep breathing exercise on reducing dyspneain heart failure patients at the Depok Regional Hospital with a p-value (p<0,05). Researchers recommend the applicationof deep breathing exercise as a form of intervention in the inpatient phase to reduce dyspnea in heart failure patients andadd variables that have not been studied.